Polymer coating, preparation method thereof, negative electrode current collector and negative-electrode-free sodium ion battery

By constructing a polymer coating on the surface of the negative electrode current collector of the sodium ion battery, the problems of low energy density and uneven sodium deposition of sodium are solved, and higher electrochemical performance and better cycling performance are achieved.

CN119505586AActive Publication Date: 2025-02-25LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411623235.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing sodium ion batteries have low energy density and uneven sodium deposition, which affects the safety and electrochemical performance of the batteries.

Method used

A polymer coating is used as the negative electrode current collector surface coating. The polymer coating consists of a polymer precursor, a photocuring initiator, an electronic conductor, an ionic conductor and a binder. Through the combination of a three-dimensional porous structure and a conductor material, it promotes the rapid transmission of electrons and ions, and forms a NaBr phase in the SEI layer to improve the stability of interface ion transport.

Benefits of technology

It significantly improves the electrochemical performance of sodium ion batteries, improves the deposition uniformity of sodium ions on the negative electrode surface and the Coulomb efficiency of charging and discharging, avoids dendrites and improves the cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505586A_ABST
    Figure CN119505586A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a polymer coating, a preparation method thereof, a negative electrode current collector and a negative-electrode-free sodium ion battery. The polymer coating provided by the invention is prepared from a coating containing a polymer precursor, a photocuring initiator, an electronic conductor, an ionic conductor and a binder, wherein the chemical structure of the polymer precursor is shown as a formula A; in the formula A, X is Br, and R is one or more of a propenyl group, a butenyl group, a propynyl group, a methyl vinyl ketone group, a 3-hepten-2-ketone group, a 5-methyl-3-hexene-2-ketone group and a 5, 5-difluoro-1-hexenyl group. The polymer coating provided by the invention is introduced into the negative-electrode-free sodium ion battery as a negative electrode current collector surface coating, and is matched with reasonable electron and ion conductors, so that the electron and ion transmission capability at a negative electrode interface can be obviously improved, the growth of sodium dendrites during a circulation period is obviously inhibited, and the electrochemical performance of the battery is obviously improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a polymer coating, a preparation method thereof, a negative electrode current collector and a negative electrode-free sodium ion battery. Background Art

[0002] Due to the scarcity of lithium resources and their uneven distribution around the world, researchers have found an element of the same family as lithium - sodium, in order to solve the problem of lithium resources. Sodium has similar physical and chemical properties to lithium. Sodium is not only abundant but also cheap. + ) has an electrode potential 0.3V higher than that of lithium ions, and its electrochemical performance is more stable and its safety performance is higher.

[0003] At present, the most commonly used current collector materials for sodium-ion batteries are copper foil or aluminum foil. Copper foil has good electrical conductivity, can effectively promote the deposition and precipitation process of sodium, and has high conductivity and mechanical strength. However, the main advantage of sodium-ion batteries is the higher cost performance. Therefore, in most cases, the negative electrode current collector uses the lower-priced aluminum foil. Unlike lithium, which easily undergoes alloying reaction with aluminum-based current collectors at low potentials at the negative electrode, the sodium negative electrode will not undergo alloying reaction with aluminum-based current collectors. Therefore, it is necessary to develop a new negative electrode material system to improve the energy density of sodium-ion batteries.

[0004] At present, sodium-ion batteries mostly use hard carbon as the negative electrode material, but due to the large specific surface area and many surface defects of the hard carbon material itself, the battery's initial charge and discharge efficiency will be low. Limited by the low capacity, low compaction and low initial efficiency of hard carbon, the energy density of sodium-ion batteries is usually less than 140Wh / kg. One solution is to directly use copper foil or aluminum foil as the negative electrode, and use the electroplating deposition and dissolution of sodium ions as the negative electrode reaction to construct a negative electrode-free sodium-ion battery to achieve extremely high energy density. However, the binding energy of traditional aluminum foil and copper foil with sodium metal ions is low, which will lead to uneven sodium deposition during charging and low battery coulomb efficiency. In addition, the volume of the negative electrode formed by sodium metal deposition will change during the cycle, affecting the safety and electrochemical performance of the battery, limiting the practical application of negative electrode-free sodium-ion batteries. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a polymer coating, a preparation method thereof, a negative electrode current collector and a negative electrode-free sodium ion battery. The polymer coating provided by the present invention is introduced into the negative electrode-free sodium ion battery as the surface coating of the negative electrode current collector, which can significantly improve the electrochemical performance of the negative electrode-free sodium ion battery.

[0006] The present invention provides a polymer coating, which is made of a coating containing a polymer precursor, a photocuring initiator, an electron conductor, an ion conductor and a binder. The chemical structure of the polymer precursor is shown in Formula A:

[0007]

[0008] Wherein, X is Br, and R is one or more of propenyl, butenyl, propynyl, methyl vinyl ketone, 3-heptene-2-one, 5-methyl-3-hexene-2-one and 5,5-difluoro-1-hexenyl.

[0009] Preferably, the polymer precursor is at least one of the compounds of formula (I) to formula (VII):

[0010]

[0011] Preferably, the polymer precursor is prepared according to the following steps:

[0012] a) subjecting an aldehyde-containing methylpyrrole monomer of formula a to a McMurray coupling reaction to obtain an intermediate compound of formula b;

[0013] b) reacting the intermediate compound of formula b with a halogenated olefin of formula c to obtain a polymer precursor of formula a;

[0014] XR type c;

[0015]

[0016] Wherein, X is Br, and R is one or more of propenyl, butenyl, propynyl, methyl vinyl ketone, 3-heptene-2-one, 5-methyl-3-hexene-2-one and 5,5-difluoro-1-hexenyl.

[0017] Preferably, the electronic conductor is one or more of graphite, acetylene black, SuperP, Super S, graphene, carbon fiber, carbon nanotube and Ketjen black; the ion conductor is a sodium solid electrolyte, whose structural formula is Na 1+x Zr2Si x P 3- x O 12 , 0≤x≤3.

[0018] Preferably, the photocuring initiator is one or more of benzoin, benzoin derivatives, benzil, alkyl phenones, acylphosphine oxides, benzophenones and thioxanthones; the binder is one or more of acrylic binder, polyvinyl alcohol and sodium carboxymethyl cellulose.

[0019] Preferably, the mass ratio of the polymer precursor, the photocuring initiator, the electron conductor, the ion conductor and the binder is 6:(0.2-2):(0.5-2):(0.5-2):(1-3).

[0020] The present invention provides a method for preparing the polymer coating described in the above technical solution, comprising the following steps:

[0021] The coating containing polymer precursor, photocuring initiator, electron conductor, ion conductor and adhesive is coated, baked and ultraviolet-cured to obtain polymer coating.

[0022] The present invention provides a negative electrode current collector, which comprises a negative electrode current collector substrate and a coating coated on the surface of the negative electrode current collector substrate, wherein the coating is the polymer coating described in the above technical solution or the polymer coating prepared by the preparation method described in the above technical solution.

[0023] Preferably, the negative electrode current collector substrate is made of aluminum.

[0024] The present invention provides a negative electrode-free sodium ion battery, wherein the negative electrode-free sodium ion battery uses the negative electrode current collector described in the above technical solution as the negative electrode.

[0025] Compared with the prior art, the present invention provides a polymer coating, a preparation method thereof, a negative electrode current collector and a negative electrode-free sodium ion battery. The polymer coating provided by the present invention is made of a coating containing a polymer precursor, a photocuring initiator, an electron conductor, an ion conductor and a binder, and the chemical structure of the polymer precursor is shown in formula A; in formula A, X is Br, and R is one or more of propenyl, butenyl, propynyl, methyl vinyl ketone, 3-heptene-2-one, 5-methyl-3-hexene-2-one and 5,5-difluoro-1-hexenyl. The present invention uses a polymer coating of a specific component as a surface coating of a negative electrode current collector of a negative electrode-free sodium ion battery. The polymer coating has a three-dimensional porous structure, and the gaps are filled with a conductor material, which can take into account the rapid transmission of electrons and ions. At the same time, the free bromine anions in the polymer coating are easily combined with sodium ions to induce the formation of a NaBr phase in the SEI layer, and NaBr has a low sodium ion diffusion barrier in the SEI layer, thereby improving the stability of interfacial ion transmission; and the cationic groups anchored in the polymer coating can make more anions in the electrolyte enriched on the negative electrode surface to participate in the negative electrode film formation through charge attraction, thereby increasing the NaF component in the SEI film, so that the sodium metal nucleation overpotential is reduced, and a sodium ion high-speed transmission channel at the negative electrode interface is constructed, thereby improving the uniformity of sodium ion deposition on the negative electrode surface, improving the coulomb efficiency of battery charging and discharging, and avoiding the growth of dendrites caused by insufficient sodium ion diffusion rate. Therefore, introducing the polymer coating provided by the present invention as the surface coating of the negative electrode current collector into a negative electrode-free sodium ion battery can significantly enhance the electron and ion transmission capacity of the battery, significantly improve the sodium dendrite growth of the battery, and improve the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0027] Figure 1 It is a comparison chart of the room temperature cycle performance of the battery of Example 9 provided by the present invention and the battery of Comparative Example 2. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The present invention provides a polymer coating, which is prepared by coating, baking and UV curing a coating containing a polymer precursor, a photocuring initiator, an electron conductor, an ion conductor and a binder. The chemical structure of the polymer precursor is shown in Formula A:

[0030]

[0031] Wherein, X is Br, and R is one or more of propenyl, butenyl, propynyl, methyl vinyl ketone, 3-heptene-2-one, 5-methyl-3-hexene-2-one and 5,5-difluoro-1-hexenyl.

[0032] In the polymer coating provided by the present invention, the polymer precursor in the coating may specifically be at least one of the compounds of formula (I) to formula (VII):

[0033]

[0034] In the polymer coating provided by the present invention, the polymer precursor is preferably prepared according to the following steps:

[0035] a) subjecting an aldehyde-containing methylpyrrole monomer of formula a to a McMurray coupling reaction to obtain an intermediate compound of formula b;

[0036] b) reacting the intermediate compound of formula b with a halogenated olefin of formula c to obtain a polymer precursor of formula a;

[0037] XR type c;

[0038]

[0039] Wherein, X is Br, and R is one or more of propenyl, butenyl, propynyl, methyl vinyl ketone, 3-heptene-2-one, 5-methyl-3-hexene-2-one and 5,5-difluoro-1-hexenyl.

[0040] In the above-mentioned polymer precursor preparation steps provided by the present invention, in step a), the specific process of carrying out the McMurray coupling reaction preferably includes: mixing the aldehyde-containing methylpyrrole monomer of formula a structure and a solvent, then reducing the temperature of the mixed system to below -10°C, then adding titanium tetrachloride to the mixed system for a period of mixed reaction, then adding zinc powder to the mixed system for a period of mixed reaction, then raising the temperature of the mixed system to above 10°C, continuing the reaction for a period of time, quenching the reaction, and post-treating the reaction product to obtain an intermediate compound of formula b structure. Wherein, the entire McMurray coupling reaction process is carried out under a protective gas atmosphere, and the protective gas is preferably nitrogen; the solvent is preferably tetrahydrofuran; the -10°C or below is preferably -15 to -20°C, more preferably -18°C; the amount ratio of the titanium tetrachloride to the aldehyde-containing methylpyrrole monomer of formula a is preferably (5 to 8) mL:50 mmol, more preferably 6.5 mL:50 mmol; the mixing reaction time after adding the titanium tetrachloride is preferably 20 to 60 min, more preferably 30 min; the zinc powder and formula a The dosage ratio of the structural aldehyde-containing methylpyrrole monomer is preferably (6-9) g:50 mmol, more preferably 7.8 g:50 mmol; the mixing reaction time after adding the zinc powder is preferably 20-60 min, more preferably 30 min; the temperature above 10°C is preferably 15-35°C, more preferably 25°C (room temperature); the continued reaction time is preferably 2-6 h, more preferably 4 h; the method of quenching the reaction is preferably quenching with ice water; the post-treatment method preferably includes extraction, rotary evaporation to remove the solvent and column chromatography in sequence.

[0041] In the above-mentioned polymer precursor preparation steps provided by the present invention, in step b), the molar ratio of the intermediate compound of formula b structure to the halogenated olefin of formula c structure is preferably 50:(70-130), specifically 50:105; the reaction is preferably carried out in a protective gas atmosphere, and the protective gas is preferably nitrogen; the reaction is preferably carried out in an organic solvent, and the organic solvent is preferably acetonitrile; the reaction temperature is preferably 50-80°C, specifically 60°C; the reaction time is preferably 12-48h, specifically 24h; after the reaction is completed, the product is post-treated, and the post-treatment process preferably includes: vacuum distillation, washing and drying in sequence.

[0042] In the polymer coating provided by the present invention, the photocuring initiator in the coating is preferably one or more of benzoin, benzoin derivatives, benzyls, alkyl phenones, acyl phosphorus oxides, benzophenones and thioxanthones, more preferably α-hydroxy ketone, 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide ketone or 2-hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl) benzyl)-2-methyl-1-propanone.

[0043] In the polymer coating provided by the present invention, the electronic conductor in the coating is preferably one or more of graphite, acetylene black, SuperP, Super S, graphene, carbon fiber, carbon nanotube and Ketjen black.

[0044] In the polymer coating provided by the present invention, the ion conductor in the coating is preferably a sodium solid electrolyte, whose structural formula is Na 1+x Zr2Si x P 3-x O 12 , 0≤x≤3, x can be specifically 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3; the ion conductor is a nano powder, and its particle size is preferably 300-800nm, specifically 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm or 800nm.

[0045] In the polymer coating provided by the present invention, the binder in the coating is preferably one or more of polyacrylic acid, polyvinyl alcohol and sodium carboxymethyl cellulose.

[0046] In the polymer coating provided by the present invention, the mass ratio of the polymer precursor, the photocuring initiator, the electron conductor, the ion conductor and the binder in the coating is preferably 6:(0.2-2):(0.5-2):(0.5-2):(1-3); wherein the mass ratio of the polymer precursor and the photocuring initiator can be specifically 6:0.2, 6:0.3, 6:0.4, 6:0.5, 6:0.6, 6:0.7, 6:0.8, 6:0.9, 6:1, 6:1.1, 6:1.2, 6:1.3, 6:1.4, 6:1.5, 6:1.6, 6:1.7, 6:1.8, 6:1.9 or 6:2; the mass ratio of the polymer precursor to the electron conductor can be 6:0.5, 6:0.6, 6:0.7, 6:0.8, 6:0.9, 6:1, 6:1.1, 6:1.2, 6:1.3, 6:1.4, 6:1.5, 6:1.6, 6:1.7, 6:1.8, 6:1.9 or 6:2; :1.4, 6:1.5, 6:1.6, 6:1.7, 6:1.8, 6:1.9 or 6:2; the mass ratio of the polymer precursor to the ion conductor can be 6:0.5, 6:0.6, 6:0.7, 6:0.8, 6:0.9, 6:1, 6:1.1, 6:1.2, 6:1.3, 6 ... 6:2; the mass ratio of the polymer precursor to the binder may specifically be 6:1, 6:1.1, 6:1.2, 6:1.3, 6:1.4, 6:1.5, 6:1.6, 6:1.7, 6:1.8, 6:1.9, 6:2, 6:2.1, 6:2.2, 6:2.3, 6:2.4, 6:2.5, 6:2.6, 6:2.7, 6:2.8, 6:2.9 or 6:3.

[0047] In the polymer coating provided by the present invention, the coating further contains a solvent, and the solvent is preferably ethanol.

[0048] In the polymer coating provided by the present invention, the solid content of the coating is preferably 10-60%, specifically 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.

[0049] The present invention also provides a method for preparing the polymer coating described in the above technical solution, comprising the following steps:

[0050] The coating containing polymer precursor, photocuring initiator, electron conductor, ion conductor and adhesive is coated, baked and ultraviolet-cured to obtain polymer coating.

[0051] In the preparation method provided by the present invention, the specific information of each component in the coating has been introduced above and will not be repeated here.

[0052] In the preparation method provided by the present invention, the coating thickness is preferably 1.5 to 3 μm, specifically 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm or 3 μm.

[0053] In the preparation method provided by the present invention, the baking temperature is preferably 80-120°C, specifically 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C; the baking time is preferably 20-60s, specifically 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s or 60s.

[0054] In the preparation method provided by the present invention, the ultraviolet lamp used for ultraviolet curing is preferably 10 to 15 cm away from the coating surface, specifically 10 cm, 11 cm, 12 cm, 13 cm, 14 cm or 15 cm; the power of the ultraviolet lamp is preferably 2 to 3 kW; the time of the ultraviolet curing is preferably 10 to 15 s, specifically 10 s, 11 s, 12 s, 13 s, 14 s or 15 s.

[0055] The present invention also provides a negative electrode current collector, comprising a negative electrode current collector substrate and a coating coated on the surface of the negative electrode current collector substrate, wherein the coating is the polymer coating described in the above technical solution or the polymer coating prepared by the preparation method described in the above technical solution.

[0056] In the negative electrode current collector provided by the present invention, the material of the negative electrode current collector substrate is preferably aluminum; and the coating is preferably coated on both the front and back surfaces of the negative electrode current collector substrate.

[0057] The present invention also provides a method for preparing the negative electrode current collector described in the above technical solution, comprising the following steps:

[0058] A coating containing a polymer precursor, a photocuring initiator, an electron conductor, an ion conductor and a binder is applied to the surface of the negative electrode current collector substrate, baked, and UV-cured to form a coating to obtain a negative electrode current collector. The specific information of each component in the coating, the coating thickness, the baking and UV-curing conditions can be referred to above and will not be repeated here.

[0059] The present invention also provides a negative electrode-free sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is the negative electrode current collector described in the above technical solution.

[0060] In the negative electrode-free sodium ion battery provided by the present invention, the positive electrode includes a positive electrode current collector and a positive electrode coating coated on the surface of the positive electrode current collector; the positive electrode current collector includes but is not limited to aluminum foil; the components of the positive electrode coating include positive electrode active materials, conductive agents and binders. In the present invention, the positive electrode active materials are preferably sodium iron sulfate, nickel iron manganese layered oxide, sodium iron phosphate pyrophosphate and sodium copper iron manganese (Na 0.9 Cu 0.22 Fe 0.30 Mn 0.48 O2) at least one; the conductive agent is preferably carbon nanotubes (CNT); the binder is preferably polyvinylidene fluoride (PVDF); the mass ratio of the positive electrode active material, the conductive agent and the binder is preferably 97.4: (0.5 ~ 3): (0.5 ~ 3), more preferably 97.4: 1.3: 1.3.

[0061] In the negative electrode-free sodium ion battery provided by the present invention, the diaphragm is preferably a polypropylene diaphragm, a polyethylene diaphragm or a polyethylene diaphragm coated with aluminum oxide on one side, more preferably a polyethylene diaphragm coated with aluminum oxide on one side.

[0062] In the negative electrode-free sodium ion battery provided by the present invention, the electrolyte is preferably a diethylene glycol dimethyl ether solution of sodium hexafluorophosphate; the content of the sodium hexafluorophosphate in the electrolyte is preferably 0.5-2 mol / L, specifically 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2 mol / L.

[0063] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects:

[0064] (1) The free bromine anions in the polymer coating on the surface of the negative electrode current collector provided by the present invention are easily combined with sodium ions to induce the formation of a NaBr phase in the SEI layer, and NaBr has a low sodium ion diffusion barrier in the SEI layer, thereby improving the interfacial ion transport stability.

[0065] (2) The polymer coating on the surface of the negative electrode current collector provided by the present invention has a three-dimensional structure, and the sodium solid electrolyte particles preferably filled in the gaps serve as fast ion conductors, which can give sodium ions the ability to quickly transport in the gaps, effectively avoiding the interfacial sodium precipitation caused by polarization, thereby improving the safety performance of the negative electrode-free sodium ion battery.

[0066] (3) The polymer coating on the surface of the negative electrode current collector provided by the present invention is anchored with cationic groups. The cationic groups can make more anions in the electrolyte participate in the negative electrode film formation through charge attraction, thereby increasing the NaF phase in the SEI film. The NaF phase with high Young's modulus is matched with the NaBr phase with low diffusion barrier, so that the nucleation overpotential of sodium metal on the negative electrode surface is reduced, the uniformity of sodium ion deposition on the negative electrode surface is improved, the coulomb efficiency of battery charge and discharge is improved, and the dendrite growth caused by insufficient sodium ion diffusion rate is avoided.

[0067] (4) The negative electrode current collector provided by the present invention has both high electron and ion transport capabilities. It is directly used as a negative electrode and can significantly inhibit the growth of sodium dendrites on the negative electrode surface during cycling, thereby improving the cycle performance of the negative electrode-free sodium ion battery.

[0068] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.

[0069] Example 1

[0070] The specific steps for preparing compound (I) are as follows:

[0071] (1) Preparation of intermediate product 1, the chemical reaction formula is as follows:

[0072]

[0073] The preparation process is as follows: under nitrogen atmosphere, 100 mL of ultra-dry tetrahydrofuran and 1-methyl-2,5-dihydropyrrole-3-carboxaldehyde (5.55 g, 50.00 mmol) are added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, and then transferred to a low-temperature reactor, the temperature is adjusted to -18 ° C and stirring is started; after the system temperature reaches the preset value, titanium tetrachloride (IV) (6.50 mL) is slowly added to the system through a syringe, and the stirring reaction is continued for 30 minutes after the addition is completed; then, zinc powder (7. 80g) was added in small amounts several times, and the reaction was continued to stir for 30min after the addition was completed, and then the low-temperature reactor was removed; after the reaction system returned to room temperature, the reaction was continued for 4h, and then ice water (100mL) was added to quench the reaction; then the mixture was extracted with dichloromethane (50mL×3), the organic phases were combined, half of the solvent was first removed by rotary evaporation, and then 50g of silica gel powder was added, and the residual solvent was removed by rotary evaporation. The compounds were separated by column chromatography, and the eluent was dichloromethane. After the solvent was removed by rotary evaporation, the target intermediate compound 1 was obtained, and the yield was 90.1%. EIMS (m / z): calcd.for C 14 H 20 N4, found 190.20.

[0074] (2) Preparation of compound (I), the chemical reaction formula is as follows:

[0075]

[0076] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 1 (9.51 g, 50.00 mmol) and 150 mL of anhydrous acetonitrile to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 3-bromopropylene (12.70 g, 105.00 mmol); after the addition is completed, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours; after the reaction is completed, the acetonitrile is removed by vacuum distillation, and the mixture is washed three times with ethyl acetate (3×20 mL), and finally vacuum dried to obtain compound (I), with a yield of 94.3%. EIMS (m / z): calcd.for C 18 H 28 N2 2+ ,found 136.32.

[0077] The composite modified current collector 1 sample was prepared in the following specific steps:

[0078] The polymer precursor compound (I) is mixed with a photocuring initiator α-hydroxyketone, a conductive agent acetylene black, and a sodium solid electrolyte (Na3Zr2Si2PO 12 , particle size 500nm), binder polyacrylic acid (PAA) are mixed in a mass ratio of 6:0.5:1:1:1.5, and then anhydrous ethanol is added according to a solid content of 55%, and the slurry is evenly dispersed by a double planetary mixer; the slurry is then coated on both sides of a 13μm aluminum foil with a single-side coating thickness of 3μm, and baked at 100℃ for 30s to remove the solvent, and then a 2kW ultraviolet lamp is used to irradiate for 15s at a distance of 15cm from the coating surface for photocuring to obtain a composite modified aluminum foil current collector, and the prepared composite modified aluminum foil is then stored in a drying room with a dew point of -35℃.

[0079] Prepare the standard electrolyte sample. The specific steps are as follows:

[0080] In an argon glove box where the water and oxygen contents were both ≤0.1 ppm, sodium hexafluorophosphate was dissolved in diethylene glycol dimethyl ether with a sodium salt concentration of 1 mol / L to obtain a labeled electrolyte sample.

[0081] Prepare the experimental battery 1 sample, the specific steps are as follows:

[0082] Preparation of positive electrode: Select Na 0.9 Cu 0.22 Fe 0.30 Mn 0.48 O2 is the positive electrode material, and the positive electrode material Na 0.9 Cu 0.22Fe 0.30 Mn 0.48 O2, carbon nanotubes (CNTs, 5% by mass in NMP solution) and binder polyvinylidene fluoride (PVDF, 5% by mass in NMP solution) are weighed and mixed in a mass ratio of 97.4:1.3:1.3 (excluding the solvent). After mixing, an appropriate amount of NMP is added to control the theoretical solid content to 65%. A planetary homogenizer is used to homogenize the positive electrode slurry, and the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 13 μm. After drying, rolling and cutting, a 50 mm × 70 mm positive electrode sheet is obtained.

[0083] Preparation of diaphragm: A polyethylene diaphragm coated with aluminum oxide on one side was used as the isolation membrane and was placed in a dry room with a dew point of -35°C for 72 hours before use.

[0084] Preparation of negative electrode sheet: The composite modified aluminum foil current collector prepared above was directly used as the negative electrode, and a 52 mm×72 mm negative electrode sheet was prepared by cutting.

[0085] Preparation of battery: The battery was made in a dry room with an ambient dew point of ≤-35°C, the separator was folded in a Z shape, the positive electrode sheet and the negative electrode sheet were placed on each side, there were 12 layers of positive electrode sheets and 13 layers of negative electrode sheets, the positive electrode, separator and negative electrode were aligned and stacked in order, an alumina-surface separator was coated on the positive electrode to obtain an electrode group, and then the electrode group was fixed with polyimide tape and then the ear was welded, and then placed in an aluminum-plastic film, and then vacuum-baked at 90°C for 12h, and after cooling, the above-prepared standard electrolyte was injected at an injection coefficient of 4.0g / Ah, and finally after vacuum packaging, high-temperature infiltration, formation, aging, secondary sealing and capacity division, an experimental battery 1 with a capacity of about 2.5Ah was obtained.

[0086] Example 2

[0087] The specific steps for preparing compound (II) are as follows:

[0088] (1) Prepare intermediate 1 according to the method of Example 1.

[0089] (2) Preparation of compound (II), the chemical reaction formula is as follows:

[0090]

[0091] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 1 (9.51 g, 50.00 mmol) and 150 mL of anhydrous acetonitrile to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 3-bromobutene (14.07 g, 105.00 mmol); after the addition is completed, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours; after the reaction is completed, the acetonitrile is removed by vacuum distillation, and washed three times with ethyl acetate (3×20 mL), and finally vacuum dried to obtain compound (II), with a yield of 93.9%. EIMS (m / z): calcd.for C 20 H 32 N2 2+ ,found 150.22.

[0092] The composite modified aluminum foil 2 sample and the experimental battery 2 were prepared according to the method of Example 1, except that the polymer precursor compound (II) was used in the composite modified aluminum foil 2 sample.

[0093] Example 3

[0094] The specific steps for preparing compound (III) are as follows:

[0095] (1) Prepare intermediate 1 according to the method of Example 1.

[0096] (2) Preparation of compound (III), the chemical reaction formula is as follows:

[0097]

[0098] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 1 (9.51 g, 50.00 mmol) and 150 mL of anhydrous acetonitrile to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 3-bromopropyne (12.49 g, 105.00 mmol); after the addition is completed, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours; after the reaction is completed, the acetonitrile is removed by vacuum distillation, and the mixture is washed three times with ethyl acetate (3×20 mL), and finally vacuum dried to obtain compound (III), with a yield of 90.7%. EIMS (m / z): calcd.for C 18 H 24 N2 2+ ,found 134.17.

[0099] The composite modified aluminum foil 3 sample and the experimental battery 3 were prepared according to the method of Example 1, except that the polymer precursor compound (III) was used in the composite modified aluminum foil 3 sample.

[0100] Example 4

[0101] The specific steps for preparing compound (IV) are as follows:

[0102] (1) Prepare intermediate 1 according to the method of Example 1.

[0103] (2) Preparation of compound (IV), the chemical reaction formula is as follows:

[0104]

[0105] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 1 (9.51 g, 50.00 mmol) and 150 mL of anhydrous acetonitrile to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 1-bromo-2-keto-3-butene (15.64 g, 105.00 mmol); after the addition is completed, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours; after the reaction is completed, the acetonitrile is removed by vacuum distillation, and the mixture is washed three times with ethyl acetate (3×20 mL), and finally vacuum dried to obtain compound (IV), with a yield of 91.5%. EIMS (m / z): calcd.for C 20 H 28 N2O2 2+ ,found 164.25.

[0106] The composite modified aluminum foil sample 4 and the experimental battery 4 were prepared according to the method of Example 1, except that the composite modified aluminum foil sample 4 used the polymer precursor compound (IV), the photocuring initiator was 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide ketone (TPO), the binder was sodium carboxymethyl cellulose (CMC), the polymer precursor compound (IV) and the photocuring initiator TPO, the conductive agent SuperP, and the sodium solid electrolyte (Na3Zr2Si2PO 12 , particle size 500nm), binder CMC mass ratio is 6:0.2:2:2:3, the single-sided coating thickness of the coating slurry is 1.5μm, the baking temperature is 80℃, and the baking time is 60s.

[0107] Example 5

[0108] The specific steps for preparing compound (V) are as follows:

[0109] (1) Prepare intermediate 1 according to the method of Example 1.

[0110] (2) Compound (V) is prepared, and the chemical reaction formula is as follows:

[0111]

[0112] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 1 (9.51 g, 50.00 mmol) and 150 mL of anhydrous acetonitrile to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 1-bromo-2-keto-3-heptene (19.95 g, 105.00 mmol); after the addition is completed, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours; after the reaction is completed, the acetonitrile is removed by vacuum distillation, and the mixture is washed three times with ethyl acetate (3×20 mL), and finally vacuum dried to obtain compound (V), with a yield of 92.0%. EIMS (m / z): calcd.for C 26 H 40 N2O2 2+ ,found 206.33.

[0113] The composite modified aluminum foil 5 sample and the experimental battery 5 were prepared according to the method of Example 1, except that the polymer precursor compound (V) was used in the composite modified aluminum foil 5 sample.

[0114] Example 6

[0115] The specific steps for preparing compound (VI) are as follows:

[0116] (1) Prepare intermediate 1 according to the method of Example 1.

[0117] (2) Preparation of compound (VI), the chemical reaction formula is as follows:

[0118]

[0119] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 1 (9.51 g, 50.00 mmol) and 150 mL of anhydrous acetonitrile to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 1-bromo-2-keto-5-methyl-3-hexene (19.95 g, 105.00 mmol); after the addition is completed, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours; after the reaction is completed, the acetonitrile is removed by vacuum distillation, and the product is washed three times with ethyl acetate (3×20 mL), and finally vacuum dried to obtain compound (VI), with a yield of 90.4%. EIMS (m / z): calcd.for C 26 H 40 N2O2 2+ ,found206.28.

[0120] The composite modified aluminum foil 6 sample and the experimental battery 6 were prepared according to the method of Example 1, except that the polymer precursor compound (VI) was used in the composite modified aluminum foil 6 sample.

[0121] Example 7

[0122] The specific steps for preparing compound (VII) are as follows:

[0123] (1) Prepare intermediate 1 according to the method of Example 1

[0124] (2) Preparation of compound (VII), the chemical reaction formula is as follows:

[0125]

[0126] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 1 (9.51 g, 50.00 mmol) and 150 mL of anhydrous acetonitrile to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 1-bromo-2,2-difluoro-5-hexene (20.79 g, 105.00 mmol); after the addition is completed, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours; after the reaction is completed, the acetonitrile is removed by vacuum distillation, and washed three times with ethyl acetate (3×20 mL), and finally vacuum dried to obtain compound (VII), with a yield of 89.5%. EIMS (m / z): calcd.for C 24 H 36 F4N2 2+ ,found 214.27.

[0127] The composite modified aluminum foil 7 sample and the experimental battery 7 were prepared according to the method of Example 1, except that the polymer precursor compound (VII) was used in the composite modified aluminum foil 7 sample.

[0128] Example 8

[0129] A composite modified aluminum foil 8 sample and an experimental battery 8 were prepared according to the method of Example 1, with the difference that a polymer precursor compound (VII) was used in the composite modified aluminum foil 8 sample, the coating baking temperature was 120°C, the baking time was 20s, the ultraviolet lamp power was 3kW, the distance from the coating surface was 10cm, and the curing time was 10s.

[0130] Example 9

[0131] A composite modified aluminum foil 9 sample and an experimental battery 9 were prepared according to the method of Example 1, with the difference that the composite modified aluminum foil 9 sample used a polymerization precursor compound (VII), the photocuring initiator used was 2-hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl)benzyl)-2-methyl-1-propanone, and the conductive agent was carbon nanotubes.

[0132] Comparative Example 1

[0133] The experimental battery 10 was prepared according to the method of Example 1, except that the negative electrode current collector of the experimental battery 10 sample used a commercially available 13 μm carbon-coated aluminum foil without composite modification.

[0134] Comparative Example 2

[0135] The experimental battery 11 was prepared according to the method of Example 1, except that the negative electrode preparation process of the experimental battery 11 sample was as follows: the negative electrode material hard carbon (gram capacity 300 mAh g -1 ), conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC, deionized water solution with a solid content of 1.5%), binder styrene butadiene rubber (SBR, deionized water solution with a solid content of 48%) are mixed at a mass ratio of 94.5:2:1.5:2, and deionized water is added after mixing. The theoretical solid content is controlled to be 40%, and the negative electrode slurry is obtained by homogenization using a planetary homogenizer, and the negative electrode slurry is evenly coated on a copper foil with a thickness of 17μm. After drying, rolling, and cutting, a 52mm×72mm negative electrode sheet is obtained. The N / P ratio of the positive and negative electrodes is 1.1.

[0136] Performance Evaluation

[0137] The sodium ion batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were subjected to long cycle performance tests and high temperature cycle tests, respectively, and the test conditions were as follows:

[0138] (1) Battery long cycle test:

[0139] The prepared sodium ion battery was placed in a constant temperature room at an ambient temperature of 25°C, and charged at a constant current and constant voltage with a current of 1C and a voltage of 4.0V until the cut-off current was 0.05C, and then discharged at a constant current of 1C to a voltage of 2V, and cycled for 1000 cycles, and the capacity retention rate was recorded. The capacity retention rate of the nth cycle (%) = (the discharge capacity of the nth cycle / the discharge capacity of the first cycle) × 100%. The number of test samples was 5 cells, and the results were averaged.

[0140] (2) High temperature cycle test:

[0141] The prepared sodium ion battery was placed in a high temperature explosion-proof box at an ambient temperature of 45°C, and charged at a constant current and constant voltage with a current of 1C and a voltage of 4.0V until the cut-off current was 0.05C, and then discharged at a constant current of 1C to a voltage of 2V, and cycled for 1000 cycles, and the capacity retention rate was recorded. The capacity retention rate of the nth cycle (%) = (the discharge capacity of the nth cycle / the discharge capacity of the first cycle) × 100%. The number of test samples was 5 cells, and the results were averaged.

[0142] The test results are shown in Table 1:

[0143] Table 1 Negative current collectors and corresponding battery performance of various embodiments and comparative examples

[0144]

[0145] The performance test results of the sodium ion batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 2 are shown in Table 1. The room temperature long cycle performance of Example 9 and Comparative Example 2 is shown in Table 1. Figure 1 As shown, it can be seen that the negative electrode-free sodium ion battery made of the composite modified aluminum foil of the present invention shows a significant gain in normal temperature long cycle performance and high temperature long cycle performance compared to the negative electrode-free sodium ion battery made of the unmodified basic aluminum foil. At the same time, compared with the sodium ion battery with the negative electrode as the conventional hard carbon negative electrode, it also has significantly improved normal temperature long cycle performance and high temperature cycle performance. It is not difficult to see that the fast ion conductor polymer layer proposed by the present invention can take into account the rapid transmission of electrons and ions by constructing a three-dimensional porous composite modified fast ion conductor polymer layer on the surface of the negative electrode current collector, and at the same time induce the formation of more NaBr components in the SEI layer, so that the interfacial charge transfer has a low diffusion energy barrier, thereby improving the stability of interfacial ion transfer. At the same time, the cationic groups anchored in the polymer coating can enrich more anions in the electrolyte on the negative electrode surface through charge attraction, thereby participating in the negative electrode film formation, thereby increasing the NaF component in the SEI film, so that the sodium metal nucleation overpotential is reduced, the uniformity of sodium ion deposition on the negative electrode surface is improved, the coulomb efficiency of battery charging and discharging is improved, and the growth of dendrites caused by insufficient sodium ion diffusion rate is avoided. Therefore, when the composite modified current collector provided by the present invention is used as the negative electrode of the negative electrode-free sodium ion battery, the interface stability of the negative electrode-free sodium ion battery can be significantly improved, and the room temperature and high temperature long cycle performance of the negative electrode-free sodium ion battery can be significantly improved.

[0146] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polymer coating, characterized in that The polymer coating is made of a coating containing a polymer precursor, a photocuring initiator, an electron conductor, an ion conductor and a binder. The chemical structure of the polymer precursor is shown in Formula A: Wherein, X is Br, and R is one or more of propenyl, butenyl, propynyl, methyl vinyl ketone, 3-heptene-2-one, 5-methyl-3-hexene-2-one and 5,5-difluoro-1-hexenyl.

2. The polymer coating according to claim 1, characterized in that The polymer precursor is at least one of the compounds of formula (I) to formula (VII):

3. The polymer coating according to claim 1, characterized in that The polymer precursor is prepared according to the following steps: a) subjecting an aldehyde-containing methylpyrrole monomer of formula a to a McMurray coupling reaction to obtain an intermediate compound of formula b; b) reacting the intermediate compound of formula b with a halogenated olefin of formula c to obtain a polymer precursor of formula a; Wherein, X is Br, and R is one or more of propenyl, butenyl, propynyl, methyl vinyl ketone, 3-heptene-2-one, 5-methyl-3-hexene-2-one and 5,5-difluoro-1-hexenyl.

4. The polymer coating according to claim 1, characterized in that The electronic conductor is one or more of graphite, acetylene black, SuperP, Super S, graphene, carbon fiber, carbon nanotube and Ketjen black; the ion conductor is a sodium solid electrolyte, whose structural formula is Na 1+x Zr2Si x P 3-x O 12 , 0≤x≤3.

5. The polymer coating according to claim 1, characterized in that The photocuring initiator is one or more of benzoin, benzoin derivatives, benzil, alkyl phenone, acyl phosphorus oxide, benzophenone and thioxanthone; the binder is one or more of acrylic binder, polyvinyl alcohol and sodium carboxymethyl cellulose.

6. The polymer coating according to claim 1, characterized in that The mass ratio of the polymer precursor, the photocuring initiator, the electron conductor, the ion conductor and the binder is 6:(0.2-2):(0.5-2):(0.5-2):(1-3).

7. A method for preparing a polymer coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: The coating containing polymer precursor, photocuring initiator, electron conductor, ion conductor and adhesive is coated, baked and ultraviolet-cured to obtain polymer coating.

8. A negative electrode current collector, characterized in that: The negative electrode current collector comprises a negative electrode current collector substrate and a coating coated on the surface of the negative electrode current collector substrate, wherein the coating is the polymer coating according to any one of claims 1 to 6 or the polymer coating prepared by the preparation method according to claim 7.

9. The negative electrode current collector according to claim 8, characterized in that: The negative electrode current collector substrate is made of aluminum.

10. A negative electrode-free sodium ion battery, characterized in that: The negative electrode-free sodium ion battery uses the negative electrode current collector according to claim 8 or 9 as the negative electrode.

Citation Information

Patent Citations

  • Negative electrode including a polymetric single-ion conductor coating

    CN107275576A

  • Polyether sulfone copolymer, production method of same, and polymer electrolyte membrane including copolymer

    KR1020140026664A